THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE, AND WORK ENVIRONMENT ON THE PERFORMANCE OF MSME EMPLOYEES GOING DIGITAL - Apriyanto; Dwi Saleha; Siska Mayratih; Maman Faturohman; Ilma Darojat (AKSELERASI: Jurnal Ilmiah Nasional, 2026)
This study investigates the influence of work motivation, work discipline, and work environment on the performance of employees in micro, small, and medium enterprises (MSMEs) undergoing digital transformation. As MSMEs increasingly adopt digital technologies to enhance operational efficiency and competitiveness, employee performance becomes a critical factor in ensuring the success of this transition. This research employs a quantitative approach using survey data collected from 150 MSME employees who are directly involved in digitally supported work processes. Data were gathered through a structured questionnaire measured on a Likert scale and analyzed using Structural Equation Modelling-Partial Least Squares (SEM-PLS 3). The results indicate that work motivation has a positive and significant effect on employee performance, suggesting that motivated employees are more capable of adapting to digital work environments. Work discipline is also found to significantly influence employee performance, highlighting the importance of adherence to rules, time management, and responsibility in technology-mediated work settings. Furthermore, the work environment emerges as the strongest predictor of employee performance, emphasizing the role of supportive organizational conditions and adequate digital infrastructure. Collectively, work motivation, work discipline, and work environment explain a substantial proportion of variance in employee performance. These findings provide practical insights for MSME owners and managers in designing effective human resource strategies to support successful digital transformation.